FORMS AND MEANINGS OF ADJUNCTS IN JAMES’ FIFTY SHADES OF FREED - I Gede Pande Bayu Pratama; Ni Made Susini; Anak Agung Gede Suarjaya (Universitas Warmadewa, 2018)
This study is specifically aimed at identifying the forms of adjuncts and the meanings they carry. In order to analyze the data, descriptive-qualitative approach was applied in this research. The data are sentences which contain adverbials functioning as adjuncts and they were taken from a novel entitled Fifty Shades of Freed, written by Erika Leonard Mitchell, also known as E.L. James (2012). They were collected through library research and then presented informally by providing some examples and elaborations. There are some important points that can be concluded based on the results of analysis. First, adjuncts may appear in many forms, either phrases or clauses. Phrases forming adjuncts found in this novel are noun phrases, adverb phrases, and prepositional phrases. Meanwhile, clauses forming adjuncts which appear in this novel are finite verb clauses, non-finite verb clauses (including to-infinitive, bare infinitive, -ing participles, and -ed participles), and verbless clauses. Secondly, there are various meanings carried by adjuncts found in Fifty Shades of Freed. Adjuncts which denote space or place carry the meanings of position, direction, and distance. Adjuncts referring to time carry the meanings of time position, duration, frequency, and time relationship. Adjuncts showing process carry the meanings of manner, means, instrument, and agentive. Besides, there are also adjuncts which imply respect, cause, purpose, and concession found in this novel.